2023
DOI: 10.1097/opx.0000000000002042
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Serum Eye Drops for Dry Eye: Systematic Review

Abstract: Background Dry eye is a common condition with serious implications worldwide. The unique composition of autologous serum eye drops (AS) has been hypothesized as a possible treatment. Objectives To review the effectiveness and safety of AS. Data Sources We searched five databases and three registries up to September 30, 2022. Study Eligibility Randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…Autologous serum at various concentrations may improve both dry eye symptoms and tear film stability when compared with artificial tears. However, a recently updated review reported that changes in tear film stability measurements were not clinically important and concluded that there is insufficient evidence to recommend autologous serum use for dry eye . Variations in eligibility criteria regarding ocular surface disease definitions and the analysis methods implemented to handle cross-over trial results may explain differences in reported summary effect estimates and conclusions across autologous serum reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous serum at various concentrations may improve both dry eye symptoms and tear film stability when compared with artificial tears. However, a recently updated review reported that changes in tear film stability measurements were not clinically important and concluded that there is insufficient evidence to recommend autologous serum use for dry eye . Variations in eligibility criteria regarding ocular surface disease definitions and the analysis methods implemented to handle cross-over trial results may explain differences in reported summary effect estimates and conclusions across autologous serum reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the frequent use of unpreserved AS eye drops in outpatients around the world, there are only very few reports on infectious complications of AS eye drops [7]. A recent systematic review of AS therapy for dry eye showed that none of the six included randomized control trials reported on the safety or adverse effect of AS eye drops [8]. Hence, the aim of this study was to analyze the risk for infectious complications of unpreserved AS eye drops when used in an outpatient setting.…”
Section: Introductionmentioning
confidence: 99%